Type 2 diabetes mellitus in acute myocardial infarction: a persistent significant burden on long-term mortality - Bouisset, Frédéric; Bataille, Vincent; Schiele, François; Puymirat, Etienne; Fayol, Antoine; Simon, Tabassome; Danchin, Nicolas; Ferrières, Jean (Frontiers in Cardiovascular Medicine, 2024)
The long-term impact of type 2 diabetes mellitus (T2DM) after an acute myocardial infarction (AMI) has not been investigated in details yet. We aimed to assess the long-term impact T2DM after AMI.We analyzed the data of three nationwide observational studies from the French Registry of Acute ST-elevation and non-ST-elevation Myocardial Infarction (FAST-MI) program, conducted over a one-month period in 2005, 2010 and 2015. Patients presenting T2DM were classified as diabetic, patients presenting type 1 diabetes mellitus were excluded. We identified factors related to all-cause death at one-year follow-up and created two groups of 1897 subjects, paired on their one-year probability of death estimated by the logistic regression model.A total of 9181AMI patients were included in the analysis, among them 2038 (22.2%) T2DM.Patients with diabetes were significantly older (68.2+/-12.0 vs 63.8 +/-14.4, p<0.001) and were more likely to present a prior history of percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG) or heart failure (22.5% vs 13.0%, 7.1% vs 3.1% and 6.7 vs 3.8% respectively, p<0.001 for all). In two groups of 1897 patients matched using propensity score on their probability of death at 1 year, diabetes was still associated with long-term mortality with HR=1.30, 95%CI [1.17-1.45], p<0.001T2DM per se has an adverse impact on long-term survival after myocardial infarction: independently of the risk of short-term mortality, patients with diabetes who survived an AMI, have a 30% higher risk of long-term mortality.